Tradisi A’dangang dalam Ritual Kematian Masyarakat Suku Kajang Kabupaten Bulukunba: Perspektif Kaidah al-'Adah al-Muhakkamah - Khatimah, Husnul; Qayum, Abdul Rahman Hi Abdul (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
This study focuses on one of the rules of Islamic jurisprudence, namely the rule of Al-'adatu Muhakkamah, a customary law concept that recognizes and can use the custom as a legal basis as long as it does not conflict with Islamic law. This study aims to identify and understand the symbolic meaning contained in each stage of the death ritual tradition called A'dangang in the Kajang tribe, and to examine how the ritual tradition is in line with the principles of the rule of Al 'adatu Muhakkamah. The research method used is a field research method with a qualitative descriptive approach, where data is obtained through observation and in-depth interviews with traditional leaders, religious leaders, and the local community. In this study, the instruments used include interview guides and voice recorders. The process of managing and analyzing data is carried out through several stages, namely data reduction, data presentation, and drawing conclusions. The results of the study show that  the A'dangang death ritual tradition is not only a death ritual, but also a means of strengthening cultural identity and a symbol of respect for ancestors in the Kajang tribe. Regarding this tradition, religious figures are of the view that the practice needs to be adjusted to Islamic teachings which emphasize simplicity in the death procession and uphold Islamic law itself. From the perspective of the Al-‘adatu Muhakkamah principle, the A’dangang death ritual tradition cannot be used as a legal basis or is not in line with the Al-‘adatu Muhakkamah principle because in its series there are several processes that are considered contrary to Islamic principles such as taking off clothes as a symbol of mourning, the use of offerings, and other practices that may contain elements of shirk. This study found that the A’dangang ritual is an important part of the Kajang cultural identity that must be preserved. However, to prevent its values from changing, the preservation of this tradition must consider Islamic principles.